EVALUATION GUIDANCE OF LIQUID WASTE PROCESSING SYSTEM IN ELECTROPLATING UMKM CV. XYZ - Sobarsah, G. Awaludin; Ananda, Lintang Rizkyta; Rafiani, Alissya; Ulsak, Mohammad Ghimnastiar; Mukti, Rendi (International Journal of Engagement and Empowerment (IJE2), 2025)
Development in the industrial sector on the one hand will produce goods and services that are beneficial for the welfare of the people, and on the other hand, industrial activities will produce waste. The problem of industrial waste is increasingly worrying, especially the waste produced generally contains toxic and hazardous chemicals. One of them is waste containing heavy metals. This community research aims to assist in the evaluation of the electroplating liquid waste processing process at UMKM CV. XYZ with parameters of Cr, Zn, Cd, CN-, total suspended solids (TSS) and acidity values ​​(pH). The method used is to apply SK. MENLH. No. KEP-51 / MENLH / 10/1995, if the waste is directly disposed of into the environment it will cause pollution to other living things. Therefore, the process of reducing the concentration of metals is carried out by neutralization and coagulation, so that the metals that are discharged are in accordance with the quality standard. The results of the application concluded that the inlet concentration of chromium metal was 0.48 µg/L, zinc 1.83 mg/L, cyanide compound 0.02 mg/L, total suspended solids (TSS) 195.3 and the degree of acidity (pH) 10.6 and decreased to chromium metal 0.19 µg/L, zinc 1.48 mg/L, cyanide compound 0.0043 mg/L, total suspended solids (TSS) 52.6 and the degree of acidity (pH) 9 at the outlet that is discharged into the environment. So that the efficiency level of each parameter is obtained: TSS 73.11%, pH 12.36%, chromium metal 43.75%, zinc 19.13% and cyanide compound 78.5%.